Rescaling belonging in "Brexit Britain": Spatial identities and practices of Polish nationals in Scotland after the U.K. Referendum on European Union membership. Issue 1 (19th November 2018) - Botterill, Kate; Hancock, Jonathan
Abstract: This paper discusses how the 2016 U.K. Referendum on European Union membership has shaped the spatial identities and practices of Polish nationals living in Scotland. On the basis of original qualitative data collected in Edinburgh after the referendum, we make two key arguments. First, the referendum was a catalyst for Polish nationals to rescale spatial identities and challenge normative definitions of nationalism and citizenship. We highlight the role of emotion as a key driver in this process, showing that multiscalar attachments to place and strategies for onward mobility, adaptation, and integration after Brexit are constructed through emotionality. Second, the paper argues that Polish nationals' spatial practices have been shaped by anti‐immigrant discourse and sentiment surrounding the Brexit vote. In particular, local public spaces are viewed simultaneously as sites of potential conflict and sites of meaningful intercultural engagement and everyday citizenship. A broader aim of the paper is to advance feminist theory and praxis in population geography through a focus on nonhierarchical and relational scales of experience to better understand migrant identities and practices in a changing Europe.